2012
DOI: 10.1111/j.1399-3038.2012.01345.x
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal jaundice is a risk factor for childhood asthma: a retrospective cohort study

Abstract: Neonatal jaundice increased the rate and severity of childhood asthma in subjects aged up to 10 yr and may be a risk factor for childhood asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 20 publications
3
38
0
7
Order By: Relevance
“…The authors hypothesized that this could have been due to a drug effect, but whether the risk was due to more severe maternal disease was unable to be determined. It is important to note that prior studies have identified neonatal jaundice 16 or treatment for jaundice 17 as a predictor of childhood asthma, but these reports have not taken maternal asthma into account. Perhaps maternal asthma, which increases risk for asthma among offspring, 18 is a common cause for both neonatal jaundice and childhood asthma.…”
Section: Discussionmentioning
confidence: 99%
“…The authors hypothesized that this could have been due to a drug effect, but whether the risk was due to more severe maternal disease was unable to be determined. It is important to note that prior studies have identified neonatal jaundice 16 or treatment for jaundice 17 as a predictor of childhood asthma, but these reports have not taken maternal asthma into account. Perhaps maternal asthma, which increases risk for asthma among offspring, 18 is a common cause for both neonatal jaundice and childhood asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Four previous studies have reported the association between neonatal jaundice and asthma (11)(12)(13)(14). Two studies in Sweden conducted by Aspberg et al first reported the association of neonatal jaundice and phototherapy with childhood asthma requiring hospitalization (odds ratio = 1.27, 95% CI = 1.08, 1.50) and confirmed that neonatal jaundice and phototherapy are associated with the use of antiasthmatic drugs before 12 y of age (odds ratio = 1.30, 95% CI = 1.16, 1.47) in their subsequent analysis (11,12).…”
Section: Discussionmentioning
confidence: 99%
“…A reduction in the level of IL-2 skews the Th1/ Th2 balance toward Th2, thereby increasing the risk of atopy development (9,10). Although previous studies have reported the relationship of neonatal jaundice with childhood asthma, few studies have systemically analyzed the association between neonatal jaundice and common childhood allergic diseases (11)(12)(13)(14)(15). The prevalence of allergic diseases has risen dramatically worldwide, creating a health care burden.…”
mentioning
confidence: 99%
“…Several Taiwan studies had demonstrated the high accuracy and validity of ICD-9 diagnosis in NHIRD. Taiwan launched a national health insurance (NHI) in 1995, operated by a single-buyer, the government [7,[12][13][14]. Medical reimbursement specialists and peer review should scrutinize all insurance claims.…”
Section: Study Populationmentioning
confidence: 99%
“…Increasingly more studies have focused on early-life events, such as respiratory viral infections, that may increase the risk of childhood asthma [3][4][5]. Other perinatal risk factors-including babies born preterm, of low birth weight, with respiratory distress syndrome or neonatal jaundice, and needing positive pressure ventilation at birth-increase susceptibility to asthma [2,6,7]. Numerous studies have suggested that early exposure to infections in utero or early in life is a potentially critical risk factor in the development of allergic disease [6,[8][9][10].…”
Section: Introductionmentioning
confidence: 98%